A novel poly(vinyl carbonate-co-butyl acrylate) quasi-solid-state electrolyte as a strong catcher for lithium polysulfide in Li–S batteries. (1st February 2020) - Ye, Bei; Cai, Xiaomin; Wang, Dongya; Saha, Petr; Wang, Gengchao
Abstract: Lithium-sulfur batteries show great potential in the field of energy storage because of their high-energy density, but the shuttle effect of lithium polysulfide has seriously hindered their practical process. Quasi-solid-state electrolyte (QPE) is considered to be a promising alternative to traditional liquid electrolyte, which can improve the safety and cycling performance of lithium-sulfur batteries. Herein, a novel poly(vinyl carbonate- co -butyl acrylate) QPE with 3D crosslinked network (PEGDA-P(VCA- co -BA)) is designed to capture lithium polysulfide through a chemical adsorption of abundant ester groups. The PEGDA-P(VCA- co -BA) QPE exhibits high ionic conductivity of 2.9 mS cm −1 . In order to synergize the beneficial effect of the PEGDA-P(VCA- co -BA) QPE, the nitrogen-doped carbon nanotube film-supported sulfur/Li cells are assembled with the QPE. As-assembled lithium-sulfur batteries show high initial capacity of 1080 mAh g −1 at 0.1 C, long cycle life (capacity retention of 715 mAh g −1 after 500 cycles) and superior rate performance.